Moderation of Islamic Education in The Digital Space - Ulum, Miftachul; Mun'im, Abdul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
This Narrative of hatred, provocation and fights of sheep built by some digital media users without considering other users can easily broadcast hatred and even cause brutality. Users of digital media must be wiser and more moderate in understanding and not easily provoked. Research on moderation of Islamic education is very important for digital media users. How to understand the moderation of Islamic education within the scope of digital space. How to form a moderate attitude in the scope of digital space. How strategies realize moderation of Islamic education in digital space. The understanding of moderate souls for digital media users will greatly affect the attitude and decision so it is not easy to be provoked in reading the narratives that corner one of the groups